2021
DOI: 10.1016/j.rce.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

¿Existe transmisión materno-fetal del SARS-CoV-2 durante la gestación?

Abstract: Patients and methods: Using the Real-time Polymerase Chain Reaction techniques for SARS-CoV-2 nucleic acids, the possible presence of this germ in vaginal discharge and amniotic fluid was investigated in four pregnant Caucasian patients affected by mild acute symptoms of COVID-19 during the second trimester of pregnancy. Results: There is no laboratory evidence to suggest a possible passage of SARS-CoV-2 from the infected mother to the amniotic fluid. Conclusions: It is necessary to expand the investigation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…In one study, the presence of SARS-CoV-2 was investigated in vaginal discharge and amniotic fluid in four pregnant women with mild acute symptoms of COVID-19 who underwent amniocentesis during the second trimester of pregnancy [ 72 ]. In addition, in another study, a case of vaginal delivery without complications was described in a mother with COVID-19 [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In one study, the presence of SARS-CoV-2 was investigated in vaginal discharge and amniotic fluid in four pregnant women with mild acute symptoms of COVID-19 who underwent amniocentesis during the second trimester of pregnancy [ 72 ]. In addition, in another study, a case of vaginal delivery without complications was described in a mother with COVID-19 [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…5 Initial reports from China, where the COVID-19 infection had begun, showed that pregnant women infected with SARS-CoV-2 were not transmitting the virus to their neonates, [6][7][8][9][10] but concern remained for the potential of vertical infection. [11][12][13][14] As the COVID-19 pandemic spread to other countries and large numbers of pregnant women became infected, there were reports of neonates having positive testing for SARS-CoV-2 occurring after delivery, raising the specter that vertical transmission might be occurring. [15][16][17][18] Placental pathology criteria 19 were developed for the diagnosis of intrauterine transplacental transmission in infected maternal-fetal dyads that utilized molecular pathology methods for identifying SARS-CoV-2 in fetal cells of the placenta.…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually, if the viral particle is smaller than the barrier of the placenta, the virus might cross the placenta to infect the fetus. Some studies have investigated the possibility of vertical transmission of COVID-19, but no cases of vertical transmission have been reported [3][4][5]. This is concordant with the fact that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes COVID-19, is a large virus, and it therefore is unlikely to cross the placenta to result in vertical transmission.…”
Section: Vertical Transmissionmentioning
confidence: 86%